Respon Recipient dan Strategi Pengelolaan Berkelanjutan Sekolah Komunal Vonggo dalam Menghabituasikan Praktik Sekolah Komunitas - Fitri Handayani; Harto Wicaksono (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
The problem of education in Vonggo Village is a crucial matter that needs to be resolved immediately. The presence of the Vonggo Communal School is expected to be a beacon for the Vonggo people so that they can pursue education like other children in general. This paper aims to look at how the Vonggo Village community responds to the inclusion of education through the Vonggo Communal School and see how the Vonggo Communal School's management strategy is in habituating community school practices. The method used in this research is qualitative research with a participatory action research (PAR) approach. The problems in this study were analyzed using the Habituation theory by Pierre Bourdieu. The results showed that at the beginning of SKV's presence, there were negative responses, including 1) people's attitude which tended to be closed; 2) there is public opinion that education is not a priority; and 3) concerns about the entry of Islamization through schools. However, over time, the community began to show a positive response by starting to participate in the development of school implementation and the emergence of enthusiasm to send their children to SKV. SKV, which is still relatively new, has been running quite well, but in its implementation, there are still many problems that require various alternative solutions so that this school can run continuously.